Implementasi Kebijakan Peraturan Pemerintah Nomor 39 Tahun 2021 Tentang Penyelenggaraan Bidang Jaminan Produk Halal Pada Produk Pangan di Kota Serang Provinsi Banten - Syifa Putri Rizki; Yeni Widyastuti; Titi Stiawati (Sawala : Jurnal Administrasi Negara, 2025)
Halal product certification is seen as important for producers because it is very beneficial for product continuity. As for consumers, halal certification is very useful for providing protection for consumers from all forms of materials that are harmful to health and all matters related to the halalness of products, both ingredients and processing methods. The theory used in this research is the theory of the policy implementation model from Soren C Winter in Indiati 2021, namely behavior in inter-organizational relations, lower-level behavior (civil servants / bureaucrats); and, target group behavior. The research method used in this research is qualitative method, and this research is directed to be able to know, understand and describe the actual situation in the field in detail and actually about the implementation of Government Regulation Policy Number 39 of 2021 concerning the Implementation of the Halal Product Guarantee Field on food products in Serang City, Banten Province. The results of this study are that organizational and inter-organizational behavior in the implementation of halal product guarantees has been well implemented. Where each organization has its own role and function duties and is able to be consistent or committed to its duties and functions in accordance with existing regulations. Bureaucratic behavior as an organizational control has carried out services in accordance with applicable regulations. Positive response from policy recipients that the process of hunting   Translated with DeepL.com (free version)